The locavore's dilemma : in praise of the 10,000-mile diet - Desrochers, Pierre, 1969- (PublicAffairs, 2012)
A feisty, scrupulously-researched deconstruction of the "eat local" ethos--and how it distracts us from solving serious global food issues.